Pengaruh Pemberian Ekstrak Daun Kelor Terhadap Peningkatan Berat Badan Bayi Usia 6 -12 Bulan - Ani T Prianti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Complementary food is additional food for babies which must contain the energy and substances needed by the body. Decreased immune system has a negative impact on the health of children under five. One way is to use natural ingredients such as Moringa leaves which are processed into food that is liked by babies. The aim of this research is to determine the effect of giving Moringa leaf extract on the weight gain of babies aged 6 - 12 months in the Samata Community Health Center Working Area in 2022. The research was conducted in 2022. May 2021- December 2022. The research design used is quantitative research with a One Group Pretest and Posttest quasi-experimental design. The population is 32 babies aged 6-12 years from October - December 2021. The sampling technique is Total Sampling. Data analysis was carried out univariate and bivariate using the Paired Sample T-Test. The research results obtained from the Normality test showed a significance value of > 0.05, so the data was normally distributed, the univariate test showed that the distribution of the average increase in baby weight was 12.85 kg to 13.53 kg before and after being given Moringa leaf extract in complementary foods for breast milk. , and there was a significant influence between the baby's appetite and weight before and after being given Moringa leaf extract with a P-Value of 0.000 < 0.05. Based on the research results, it was concluded that there was a significant effect between Moringa leaf extract and increased body weight before and after administration. So it is recommended for the Samata Community Health Center to provide innovative additional food for babies to improve the nutritional status of babies at the Samata Community Health Center.